Envisioning the application of systems biology in cancer immunology - Jaitly, Tanushree; Gupta, Shailendra K.; Wolkenhauer, Olaf; Schuler, Gerold; Vera, Julio (Cancer Immunology: A Translational Medicine Context, 2020)
Biomedical research is nowadays concerned with the investigation of complex biological networks, in which dozens to thousands of proteins, genes, and miRNAs interact to control cellular or tissue-level phenotypes. Investigation of these complex biological networks requires the use of various experimental methodologies that generate massive amounts of quantitative data. In this scenario, Systems Biology emerged a decade ago as a methodological approach that combines quantitative experimental data, mathematical modeling, and other tools from computational biology, aiming to understand the regulation of these complex biochemical systems. The interaction between tumors and the immune system is not an exception to this scenario. The immune system is by definition a multiscale system not only because it involves biochemical networks that regulate the fate of immune cells, but also because immune cells communicate with each other by direct contact or through secretion of local or global signals. Furthermore, tumor and immune cells communicate, and this interaction is affected by the features of the microenvironment in which the tumor is hosted. Altogether, we are envisioning a complex multiscale biological system, whose analysis requires a systemic view to succeed integrating massive amounts of quantitative experimental data coming from different temporal and spatial scales. In this book chapter, we introduce the elements of the systems biology approach. Furthermore, we discuss some published results that suggest how systems biology can be used in the context of oncology and tumor immunology, with a focus on the development and assessment of anticancer therapies. To facilitate the reading, the chapter contains a glossary of systems biology terms.
CRIS-Team Scopus Importer:2020-06-19
Keywords: Biochemical Networks; Computational Approaches; Immunolgy; Omics; Tumor